Combined effects of river discharge regulation and estuarine morphological evolution on salinity dynamics in Yangtze Estuary, China. (5th October 2022) - Zhao, Leihua; Xin, Pei; Cheng, Haifeng; Chu, Ao
Abstract: Salinity distributions and gradients within an estuary are of great socioeconomic and ecological importance. In this study, a well-validated and process-based hydrodynamic model (Delft3D) was applied to investigate the salinity distributions and variations in the Yangtze Estuary subject to river discharge regulation by the Three Gorges Reservoir and morphological evolution of the estuary. The results indicate that the regulation of river discharge is the controlling factor for salinity variations in the estuary. Following construction of the Three Gorges Reservoir, the salinity significantly decreased during the dry season and slightly increased during the flood season. The morphological evolution of the estuary induced spatial salinity variations and affected the salinity in the estuarine wetlands (the Jiuduansha Shoal and East Chongming Mudflat). The salinity in the Jiuduansha Shoal increased from 1998 to 2010, whereas it decreased from 2010 to 2018. During the period 1998 to 2018, the salinity in the East Chongming Mudflat exhibited an increasing trend. These findings provide implications for management of water resources and wetlands in the Yangtze and other similar estuaries. Highlights: Regulation by Three Gorges Reservoir decreased salinity in Yangtze Estuary during dry season. Morphological evolution of Yangtze Estuary induced spatial salinity variations. Impact of Three Gorges Reservoir dominated that of morphological evolution.